2011
DOI: 10.1165/rcmb.2010-0427oc
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Regulates Organic Dust–Induced Airway Inflammation

Abstract: Organic dust exposure in agricultural environments results in significant airway inflammatory diseases. Gram-positive cell wall components are present in high concentrations in animal farming dusts, but their role in mediating dust-induced airway inflammation is not clear. This study investigated the role of Toll-like receptor (TLR) 2, a pattern recognition receptor for gram-positive cell wall products, in regulating swine facility organic dust extract (DE)-induced airway inflammation in mice. Isolated lung ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 39 publications
5
100
1
Order By: Relevance
“…Common biological contaminants in indoor dust include viruses, bacteria, fungi, dust mites, and pet dander (21,22). Previous reports indicate that organic dust can induce airway inflammation related with Th1/Th17 cell responses or TLR2 signaling (23,24). Our previous findings showed that indoor dust collected from bed mattress induces neutrophilic pulmonary inflammation and that EVs in indoor dust also induce neutrophilic pulmonary inflammation, which is related with Th1 and Th17 cell responses (25).…”
Section: Discussionmentioning
confidence: 88%
“…Common biological contaminants in indoor dust include viruses, bacteria, fungi, dust mites, and pet dander (21,22). Previous reports indicate that organic dust can induce airway inflammation related with Th1/Th17 cell responses or TLR2 signaling (23,24). Our previous findings showed that indoor dust collected from bed mattress induces neutrophilic pulmonary inflammation and that EVs in indoor dust also induce neutrophilic pulmonary inflammation, which is related with Th1 and Th17 cell responses (25).…”
Section: Discussionmentioning
confidence: 88%
“…Utilizing culture-dependent and culture-independent techniques, several studies have demonstrated a high burden of gram positive bacteria rather than gram negative bacteria, in organic dust samples from swine confinement buildings [18,20,41]. Previously, we demonstrated that exposure to gram positive peptidoglycan elicited airway inflammatory consequences in rodents similar to that observed with swine facility organic dust extracts, and that TLR4 in Inhalant Bioaerosol-Induced Bone Loss TLR2 signaling pathway was important in mediating airway inflammatory disease [22]. Importantly, TLR2 but not TLR4 gene polymorphisms were demonstrated by others to be associated with lung function among swine workers [21].…”
Section: Discussionmentioning
confidence: 75%
“…inhalation exposure animal model was utilized whereby mice were lightly sedated under isoflurane and received treatment with 50 μl of sterile saline (PBS) or 12.5% ODE (50 μl volume) daily for 3 weeks [22,30,34]. Animals were euthanized and measurements taken 5 hours following the final inhalation treatment.…”
Section: Exposure Animal Modelmentioning
confidence: 99%
See 2 more Smart Citations